(3HgLI GdCSQGQ heYOf GdCfhGQs - (3Ydj Hf jhSa Hf MQjR Hf eYVGO GddNej, CHh GdMSf, GdTWfhaj,J (B713 (3g` s
(3ChdgG (B:s
(3CSJaJM HGH GdYhf HCjOi eMGeO Gddg YR hLd cdgG (B,(3HYO aEfi cfJ SFdJ Cf CLeY eG hbY di bi bhd SjOfG GdLjdi aGSJNQJ Gddg JYGdi hCLHJ GdSGFd s
(3BNQgG (B:s
(3SeYJ CNj GdTjN EHQGgje jbhd (B: (3SjOi eMi GdOjf YHO GdbGOQ SjOfG hTjN GdeMbbjf Je GdcJGH GdeHGQc HMeO Gddg JYGdi s
(3ai PcQ cQGeGJ TjN GdTjhN GdCcGHQ GdbWH GdLjdi YHO GdbGOQ hehdOg hefTCg hbQGAJg heTGjNg hJdGePJg hHYV ef CNP Yfg hCNHGQ GdeTGjN Yfgs
(3fSNI eKHJg GdCSGfjOs
(3hjdi GdcJGH HYV CbhGd GdUhajI hCTYGQges
(3hYdi GdfSNI JedcGJ eMOKI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs